Communication Strategy in Handling Land Boundary Disputes at the Land Office of Lhokseumawe City - Maisyarah Maisyarah; Humaizi Humaizi; Dewi Kurniawati (Riviera Publishing, 2024)
This research aims to determine the communication strategy used by the Dispute Control and Handling Section of the Lhokseumawe City Land Office in managing land boundary disputes. The main theories and concepts used are communication strategy, organizational communication, and persuasive communication. This research uses a qualitative approach with a case study method, data collected through observation and interviews with employees involved in handling land boundary disputes. The results of this study found that the Lhokseumawe City Land Office uses a caucus process in its communication strategy in handling disputes, in contrast to the more commonly used direct mediation approach. The stages of dispute handling are in accordance with Hafied Cangara's five-step communication planning model. Analysis of the communication dimensions shows that internal communication occurs both vertically and horizontally through meetings, phone calls, and WhatsApp messages, involving reciprocal exchanges between leaders and employees and between employees. External communication involves the office acting as a facilitator during meetings. Persuasive techniques identified include integration, which involves negotiation, and fear induction, which highlights the potential consequences of unresolved disputes. The implications of this research underscore the importance of structured communication planning and strategy in effective dispute management. The findings suggest that other government agencies may benefit from adopting a similar approach. The use of effective persuasive techniques can improve the efficiency of dispute resolution.